Pengembangan Media Video Pembelajaran IPA Berbasis Kontekstual pada Pembelajaran di SD - Rahmi, Laili; Nukman, Muhamad; Fitriyeni, Fitriyeni; Lingga, Leny Julia (ANTHOR: Education and Learning Journal, 2023)
This study aims to develop a contextual-based learning video media for elementary school. The form of this research is research and development or research and development using the Four-D (4D) model. Given the length of time and cost required, the research on the development of contextual-based learning video media was onlycarried out in three stages, namely define, design, and development. The sampling technique used by researchers was a purposive sampling technique with a total sample taken of 10 students from three schools in the Pelalawan region, Riau Province. The data collection technique used was obtained from validation results by learning mediaexpert validators, material experts, and class science teachers. The data analysis technique used is descriptive analysis. The results of this study are in the form of learning video-based desain media on human respiratory system material in the form of video (mp4) which is tested based on the validator's assessment. The results ofvalidation by learning media experts show that the learning media developed is very feasible to use, based on the results of validation from experts, prereview including teachers and limited tests through student responses obtained from biology learning video media products on the subject matter of the human circulatory system are directed to the very category suitable for use as a medium for learning biology.